The Influence of Perceived Risk, Personality Traits and Products Marketing Strategy on Online Buying Behaviour for Smart Gadgets Among Millennials in Kuala Lumpur, Malaysia - Danial, Muhamad; Ahmad, Noraini; Yahaya, Syazwani (Electronic Journal of Business and Management, 2024)
The purpose of this research is to identify the impact of these variables on the online purchasing behavior of millennials in Kuala Lumpur, Malaysia, and to comprehend how these factors shape their attitudes towards shopping for smart gadgets online. The research aims to provide valuable insights to marketers, retailers, and policymakers in Malaysia by examining the specific factors that influence the online buying behavior of millennials. The insights gained from this research will help businesses and policymakers develop effective marketing strategies and policies that cater to the unique preferences and needs of the millennial generation. In this research, a deductive methodology is deemed the most suitable research strategy as it enables accurate results and precise generalisation of data applicable to the study. In this research endeavor, primary data will be obtained from participants through a questionnaire that will be disseminated electronically. Based on the Malaysian population size, the study aims to recruit a sample of 200 participants. Based on the outcomes of this research, it is evident that two independent variables, namely Personality Traits and Product Marketing Strategy, wield substantial influence over online buying behavior among millennials in Kuala Lumpur, Malaysia. In contrast, the variable of perceived risk demonstrates minimal or negligible significance in relation to the online buying behavior exhibited by this demographic. As researchers embark on further exploration, the insights gleaned from this study serve as a valuable reference point, paving the way for a deeper comprehension of the multifaceted dynamics underlying online buying behavior among millennials in Kuala Lumpur, Malaysia.